2011
DOI: 10.1039/c1sm05191a
|View full text |Cite
|
Sign up to set email alerts
|

Control of initial endothelial spreading by topographic activation of focal adhesion kinase

Abstract: The time required to re-establish a functioning endothelial cell layer after vascular implant placement is critical to the success of the respective cardiologic or surgical intervention. Topographic modifications of implant surfaces promise to expedite endothelial regeneration by triggering the activation of cellular machineries that facilitate cell spreading. Exploiting nanoimprint lithography techniques on cyclic olefin copolymer foils, we engineered biocompatible submicron-and micro-structured gratings with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
136
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(146 citation statements)
references
References 37 publications
(56 reference statements)
10
136
0
Order By: Relevance
“…Interestingly, the size of focal adhesions was visibly increased on gratings and in the presence of flow (Supplementary Figure 2a), indicating a stronger adhesion to the substrate [16]. The alignment of the actin cytoskeleton and of focal adhesions confirms the results of cell polarization (Figure 2d and Supplementary Figure 2b): EC polarization in the monolayer was induced both by gratings and by flow.…”
Section: Effect Of Substrate Topography and Wss On Endothelial Monolasupporting
confidence: 71%
See 3 more Smart Citations
“…Interestingly, the size of focal adhesions was visibly increased on gratings and in the presence of flow (Supplementary Figure 2a), indicating a stronger adhesion to the substrate [16]. The alignment of the actin cytoskeleton and of focal adhesions confirms the results of cell polarization (Figure 2d and Supplementary Figure 2b): EC polarization in the monolayer was induced both by gratings and by flow.…”
Section: Effect Of Substrate Topography and Wss On Endothelial Monolasupporting
confidence: 71%
“…The effect of topographical features with size and orientation similar to those presented by the extracellular matrix has been analyzed previously using substrates engineered by means of nanoimprint lithography [14][15]. These studies demonstrated that surface texture affects migration and polarization of individual ECs substantially [16][17]. Contact guidance is responsible for these effects.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The surface microstructure has been reported to play an important role in cell adhesion even when the other variances (e.g., composition) were fixed [102]. Previous in vitro studies using HUVECs and polymer-based substrates reported the ability of surface topography in the nm [103] and μm [104] ranges to accelerate cell adhesion, and to modulate proliferation [105]. Additionally, the surface elemental composition of this in vitro study closely resembled the post-implantation surface reported previously for an in vivo study in a murine artery [106].…”
Section: Discussionmentioning
confidence: 99%